Child Care and Cortisol Across Infancy and Toddlerhood: Poverty, Peers, and Developmental Timing. Issue 1 (February 2016) - Berry, Daniel; Blair, Clancy; Granger, Douglas A.; ,
Abstract: Evidence suggests that relations between child care and children's development—behaviorally and physiologically—likely differ between children from high‐ versus low‐risk contexts. Using data from the Family Life Project ( N = 1, 155), the authors tested (a) whether within‐ and between‐child differences in children's child care experiences (i.e., quantity, type, caregiver responsivity, and peer exposure) were predictive of their cortisol levels across infancy and toddlerhood and (b) whether these relations differed for children experiencing different levels of environmental risk. They found some evidence of such interactive effects. For children from high‐risk contexts, within‐child increases in child care hours were predictive of cortisol decreases. The inverse was evident for children from low‐risk contexts. This relation grew across toddlerhood. Whereas a history of greater center‐based child care was predictive of heightened cortisol levels for low‐risk families, this was not the case for children from high‐risk families. Irrespective of risk, greater peer exposure (between children) was associated with lower cortisol levels.